2006
DOI: 10.1007/s10067-005-1165-y
|View full text |Cite
|
Sign up to set email alerts
|

Association of systemic and thyroid autoimmune diseases

Abstract: Systemic and thyroid autoimmune diseases often overlap with each other. HT and GD may be most common among MCTD, SSc and SS patients. On the other hand, these systemic diseases are often present in HT subjects. Therefore it is clinically important to screen patients with systemic autoimmune diseases for the co-existence of thyroid disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(112 citation statements)
references
References 21 publications
4
106
1
1
Order By: Relevance
“…The presence of thyroid disease is particularly characteristic of type II and type III MGA syndromes, being associated with Addison's disease and diabetes mellitus respectively [31]. Several MGA syndromes including Hashimoto's thyroiditis and autoimmune diseases not involving endocrine glands have been described (pernicious anaemia, vitiligo, chronic muco-cutaneous candidiasis, systemic lupus erythematosus, rheumatoid arthritis and systemic sclerosis) [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of thyroid disease is particularly characteristic of type II and type III MGA syndromes, being associated with Addison's disease and diabetes mellitus respectively [31]. Several MGA syndromes including Hashimoto's thyroiditis and autoimmune diseases not involving endocrine glands have been described (pernicious anaemia, vitiligo, chronic muco-cutaneous candidiasis, systemic lupus erythematosus, rheumatoid arthritis and systemic sclerosis) [32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…Autoimmune thyroiditis has been shown to coexist in about 23% of Sjögren syndrome diagnoses [5] and the prevalence of autoimmune thyroiditis among patients with Sjögren syndrome has been reported as 18% to 24%, respectively [7,8,23]. Autoimmune hepatitis is frequently a comorbid presentation with autoimmune thyroiditis (18.3%) and Sjögren syndrome (8.4%) [24].…”
Section: Discussionmentioning
confidence: 99%
“…Centanni et al [4] reported that about one-third of patients who presented with autoimmune thyroid disease also had atrophic gastritis. Interestingly, some investigations have reported that 20% to 24% of patients with autoimmune thyroiditis also present with Sjögren syndrome [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…However, it is not clear how . Another study revealed chronic thyroiditis was found 21% of MCTD patients 11) . These data suggests physicians should be alert about chronic thyroiditis when they encounter patients with MCTD.…”
Section: Case Reportmentioning
confidence: 95%